The inaccuracy of national character stereotypes - McCrae, Robert., R.; Bratko, Denis; Chan, Wayne; Jussim, Lee; Fruyt, Filip De; Löckenhoff, Corinna E.; Bolle, Marleen De; Costa, Paul T Jr; Hřebíčková, Martina; Graf, Sylvie; Realo, Anu; Allik, Jüri; et al. (2013)
Consensual stereotypes of some groups are relatively accurate, whereas others are not. Previous work suggesting that national character stereotypes are inaccurate has been criticized on several grounds. In this article we (a) provide arguments for the validity of assessed national mean trait levels as criteria for evaluating stereotype accuracy ; and (b)report new data on national character in 26 cultures from descriptions (N=3, 323) of the typical male or female adolescent, adult, or old person in each. The average ratings were internally consistent and converged with independent stereotypesof the typical culture member, but were weakly related to objective assessments of personality. We argue that this conclusion is consistent with the broader literature on the inaccuracy of national character stereotypes.
Projekt MZOS
ENG